Statistical Process Control (SPC) on laboratory equipment: An ISO/IEC guide 25 requirement - Lacanilao, Romela J. (Animo Repository, 1998)
Quality decisions of management rely on the quality of results obtained from the measurement system of the laboratory. The validity of test results is greatly affected by different factors that comprise a process: man, method, material, equipment, and environment. Thus, the control on the process through statistical technique is imperative to achieve reliable results, and eventually, a quality management.The study focuses on the application of Statistical Process Control on the laboratory equipment to monitor the reliability of test results. This is in relation to the application of Panlab for ISO/IEC Guide 25 certification.Several equipment with the corresponding ASTM methods were investigated through control chart method. Two standard materials were used daily in the collection of data. After obtaining at least 20 data points, the individuals and range charts were constructed. Based on the patterns of the points plotted on both charts, interpretations on the process condition were then undertaken. The possible sources of variations were identified and eliminated and the necessary corrective actions were carried out. After establishing the control limits of the individual equipment, test runs were conducted to monitor the process. Also, the capability of the process to fall within the repeatability limits based on ASTM was evaluated.